Design of a smart device ecosystem for remote health and safety monitoring of infants under one year of age - Weelkly Prendigan, Gilberto Antonio (2025)
Most people have likely heard of parents facing tragic experiences with their newborns or infants under a year old. In these cases, when a parent's attention was briefly elsewhere, the child suddenly experienced a health event that, in the worst cases, led to death. These events, often referred to as “crib death,” are characterized by the wish of having had an alarm system to alert parents while intervention was still possible. This issue led to the development of “Im’Ok,” an ecosystem of smart devices designed to be an essential ally in providing peace of mind to parents and caregivers of infants under one year old by efficiently alerting them in the event of an unexpected health episode in their child. The development of “Im’Ok” followed the methodology taught by the School of Industrial Design Engineering, specifically in the Design V course. This process involved identifying the problem, performing technical documentation of the solution, analyzing gaps in market references, conducting interviews with parents, validating prototypes, and using other techniques. This approach culminated in a comprehensive ecosystem of three devices and an app that work together to ensure an intuitive experience and provide peace of mind for parents and caregivers.